Analisis Pengaruh Rasio Aktivitas Terhadap Rasio Profitabilitas Pada PT. Nippon Indosari Corpindo Tbk - Indah Permata Sari; Muhamad Rimawan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The aims of this research are (1) to determine whether there is a significant influence between total asset turnover on return on equity at PT. Nippon Indosari Corpindo Tbk. (2) To determine whether there is a significant influence between cash turnover on return on equity at PT. Nippon Indosari Corpindo Tbk. (3) To determine whether there is a significant influence between Inventory turnover on Return on equity at PT. Nippon Indosari Corpindo Tbk. (4) To determine whether there is an effect of Total asset turnover, Cash turnover, and Inventory turnover Simultaneously on Return on equity at PT. Nippon Indosari Corpindo Tbk. This type of research is associative research, where the population is the financial statements of PT. Nippon Indosari Corpindo Tbk for 12 years with a sample of 10 years. Samples were taken by purposive sampling technique. The data analysis method used is the classical assumption test, multiple linear regression analysis, correlation coefficient, determination coefficient, T test and F test. Based on the results of data analysis using the t test and f test, it shows that (1) Total assets turnover partially does not have effect on Return on equity at PT. Nippon Indosari Corpindo Tbk. (2) Cash turnover partially has no effect on Return on equity at PT. Nippon Indosari Corpindo Tbk. (3) Inventory turnover partially has no effect on Return on equity at PT. Nippon Indosari Corpindo Tbk. (4) Total assets turnover, Cash turnover, and Inventory turnover simultaneously have an influence on Return on equity at PT. Nippon Indosari Corpindo Tbk.